Morphological and Syntactic Properties of Conjunction KHOT’… KHOT’... and Its Semantics - V. N. Zavialov; Lianmei Li (Научный диалог)
The object of the article is the conjunction khot’… khot’..., and the subject is its morphological and syntactic properties. The relevance of the work lies in its direct focus on solving problems related to the description of the service fund of the Russian language. The scientific novelty is due to the fact that for the first time in Russian studies, the semantics of the conjunction khot’… khot’... is described on the basis of its constructive properties, which are characterized by the word forms related to the union, the principles of their relationship with each other, as well as external links with the syntactic structures in which they are involved. The theoretical significance lies in the proposed description algorithm, which can be used to characterize similar means of syntactic communication. It has been established that the semantics of the conjunction khot’… khot’... is focused on the minimum that the speaker and listener should be content with, and is also closely related to the category of desirability, due to the internal form of its structural components, etymologically ascending to the basis of the presentfuture tense of the verb want. Proceeding from this, the semantics of the conjunction khot'… khot'... can be defined as the desire of the speaker to fulfill himself or to provide the listener with a free, but at the same time minimally sufficient choice from the proposed alternatives both in the upper and lower semantic limits.